Social capital and good governance in Kenyan public provisioning - Miruka, Collins Ogutu (My University, 2008)
In the past decade and a half or so, the pace of civil service reforms in Africa has increased with high profile donor support as well as a growing demand locally for improved service delivery, greater accountability and more transparency. The development partners have promoted the enhancement of an agreed set of principles that characterizes these good governance initiatives. The thesis considers good governance characterized by the elimination of waste, fraud and abuse as well as a diligent regard for the rule of law. The major strategic development partners considered here include the World Bank, the United Nations Development Programme (UNDP), the Organization of Economic Co-operation and Development (OECD) and the European Union (EU). The thesis argument is that at present, the nature of social capital amongst the various Kenyan publics is a threat to the entrenchment of good governance principles in the civil service as espoused by major development partners. An attempt is made to interrogate the two concepts of good governance and social capital vis-à-vis the current trends of civil service reforms in Kenya. To develop the thesis, an international survey of the literature on good governance and social capital was carried out concurrently with a situational analysis of the Kenyan public provisioning in order to pinpoint policy implications for future reforms. This was done in order to obtain a theoretical angle to the major concerns of good governance that privilege participation and responsiveness in public provisioning. To answer pertinent questions in this regard, the Kenyan health sector was chosen as a mirror with which to analyze public provisioning in Kenya. The health sector was chosen because of the convenience it offers in terms of access as well as due to the fact that it makes it easy to interview and survey both the community of users as well as the service providers in one place (the hospital). The major finding was that abundant stocks of social capital exist amongst the various Kenyan publics; but it is mainly of the bonding and bridging type. There is need for society-wide civic education to inculcate the third element, that of linking social capital, in order to transcend the limitations of nepotism, tribalism, cronyism and other forms of corruption in public provisioning.
Keywords: Social capital; Good governance